1986
DOI: 10.1002/ccd.1810120115
|View full text |Cite
|
Sign up to set email alerts
|

Angioplasty at coronary bifurcations: Single‐guide, two‐wire technique

Abstract: A technique is described for angioplasty at coronary bifurcations. This simple approach utilizes a single guiding catheter, an exchange wire, and a conventional dilatation catheter and guidewire. With this "protective" guidewire technique, side branches at risk from occlusion during dilatation of a primary coronary segment can be protected and dilated secondarily; continual access to the threatened side branch is maintained with a "standby" exchange wire in the branch vessel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…Utilizing two separate guide systems increases the inherent risk of complications from a second arterial access site as well as the potential for trauma to the left main coronary artery because of excessive manipulation of both guides in the coronary orifice. Recently, these concerns have been addressed by Oesterle et al [ 6 ] , who described the alternative use of a conventional dilatation catheter placed down the main vessel and a steerable exchange guidewire advanced through the same guiding catheter to protect the side branch. If after the primary dilatation the side branch requires dilatation, the balloon catheter is then withdrawn and is advanced over the exchange wire into the side branch to perform dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing two separate guide systems increases the inherent risk of complications from a second arterial access site as well as the potential for trauma to the left main coronary artery because of excessive manipulation of both guides in the coronary orifice. Recently, these concerns have been addressed by Oesterle et al [ 6 ] , who described the alternative use of a conventional dilatation catheter placed down the main vessel and a steerable exchange guidewire advanced through the same guiding catheter to protect the side branch. If after the primary dilatation the side branch requires dilatation, the balloon catheter is then withdrawn and is advanced over the exchange wire into the side branch to perform dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…To protect side branches, which supply significant regional myocardium and would otherwise be bypassed surgically, proponents of the single-guidehwo- [1][2][3][4] or three- [5] wire technique have stated that their approach required only one guiding catheter and one (usually femoral) puncture site. Alternatively, the two-guidehwo-dilatation catheter-wire proponents [6-111 have indicated that their approach offered immediate availability of and simultaneous (or sequential) usage of both dilatation catheters in the coronary arterial system.…”
Section: Introductionmentioning
confidence: 99%
“…The risk is increased if there is an eccentric lesion at the bifurcation site and a stenosis in the ostium of the side branch [4]. To lower the risk of plaque shift, the "kissing" balloon technique was developed [5]. However, the results after balloon dilatation of bifurcation lesions are frequently suboptimal with a high incidence of complications and restenosis [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%